Déficit hídrico, secagem parcial da zona radicular e cobertura morta no cultivo de pimenta de cheiro - Silva, Valsergio Barros da (2022)
Studies on partial root drying (SPR) and deficit irrigation (DI) combined with soil mulch in sweet pepper, as well as studies on the economic viability of this combination, are scarce, therefore, the objective of this work was to evaluate the physiological, productive and economic effects of sweet pepper irrigated by partial drying of the root zone, deficit irrigation and full irrigation with and without soil cover. The study was carried out in the semi-arid region of Ceará, in the experimental years 2018 and 2019. The experimental design was in randomized blocks with split plots, with four replications. The primary treatment (plots) consisted of five irrigation strategies: Full irrigation (IP), 100% of ETc; deficit irrigation, ID40 and ID70, 40% and 70% of ETc, respectively; and partial drying of the root system SPR40 and SPR70, 40 and 70% of ETc, respectively. In the SPR40 and SPR70 treatments, water was provided on one side of the root system, while the other side of the root zone remained without water, the sides being alternated every seven days. In the IP, ID40 and ID70 treatments, water was provided only on one side of the root system with an emitter. Secondary treatments (subplots) consisted of two mulch levels (0 and 21 t ha−1). At 60 days after transplanting, evaluations of the physiological variables were carried out at both times, namely: net photosynthetic rate, stomatal conductance, leaf transpiration rate, internal CO2 concentration, carboxylation efficiency, instantaneous water use efficiency and the photosynthetic pigments. Productive data, number of fruits, fruit fresh mass, crop productivity and irrigation water productivity were evaluated. Economic data were analyzed, net present value, internal rate of return and the recovery time of the “payback” capital. The results indicated that full irrigation promoted better productive, physiological and economic performance. However, in a situation of water scarcity, the use of SPR70 and ID70 and the use of bagana is a financially viable alternative, as it promotes greater water savings and this conjectures a positive result, as it offers a reduction in the cost of production, maintaining satisfactory results. physiological and productive factors of culture.